2002
DOI: 10.1016/s0004-9514(14)60277-4
|View full text |Cite
|
Sign up to set email alerts
|

Waking cervical pain and stiffness, headache, scapular or arm pain: Gender and age effects

Abstract: A random population-based study using a structured telephone questionnaire was undertaken to determine the frequency, duration and prevalence of waking cervical spine pain and stiffness, headache, and aching between the scapulae or in the arm and their relationship to age and gender. Seventy-six per cent of households contacted completed the questionnaire, yielding a total of 812 questionnaires. Subjects most commonly reported waking with scapular or arm pain (27%) followed by headache (19%), cervical pain (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…The data collection process and a summary of the survey questions is reported elsewhere (7,8,24). Study 2 collected data prospectively for a week on each trial pillow [five experimental pillows and "own" pillow].…”
Section: Study Measurement Periodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data collection process and a summary of the survey questions is reported elsewhere (7,8,24). Study 2 collected data prospectively for a week on each trial pillow [five experimental pillows and "own" pillow].…”
Section: Study Measurement Periodsmentioning
confidence: 99%
“…This study examined only side sleepers with no recent history of injury or accident to the cervico-thoracic spine (8). No information was collected in either study on the type of mattress on which subjects slept, or the effect of sleeping with a partner, thus the "fit" of pillow to body shape on the mattress was not investigated.…”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…International figures indicate that at any point in time approximately 10-15% of the population will be suffering an episode of neck pain, and 40% will suffer neck pain during a 12-month period (Ariens et al 1999). Figures for the Australian population are lacking, although one survey reported that 18% of individuals woke with cervical pain and 4% suffered from it all day (Gordon et al 2002).…”
Section: Introductionmentioning
confidence: 99%